2002
DOI: 10.1046/j.1365-2656.2002.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Connectance in stream food webs

Abstract: Summary1. The properties of food webs are important both in theoretical ecology and environmental management, yet remain elusive. Here, we examined 12 new stream food webs of higher taxonomic resolution and completeness than any previously published data set and combined them with other 10 published stream webs. 2. Compared with most previously published food webs, these stream communities (containing between 22 and 212 species) had more feeding links per species, a higher fraction of intermediate species (0·7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
51
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 49 publications
11
51
1
1
Order By: Relevance
“…Animal material was only found to be the main food type (14.95%) of an omnivore T. lentiginos. These feeding patterns can be compared to others reported in tropical and temperate streams of Asia, Europe and USA (BENKE and WALLACE, 1980;WALLACE and BENKE, 1984;BRIAND, 1985;WINEMILLER, 1990;LANCASTER and ROBERTSON, 1995;SCHMID-ARAYA et al, 2002b;MANTEL et al, 2004). Detritus plays an important role in stream food webs as the key source of energy and nutrients for macroinvertebrates.…”
Section: Discussionmentioning
confidence: 69%
“…Animal material was only found to be the main food type (14.95%) of an omnivore T. lentiginos. These feeding patterns can be compared to others reported in tropical and temperate streams of Asia, Europe and USA (BENKE and WALLACE, 1980;WALLACE and BENKE, 1984;BRIAND, 1985;WINEMILLER, 1990;LANCASTER and ROBERTSON, 1995;SCHMID-ARAYA et al, 2002b;MANTEL et al, 2004). Detritus plays an important role in stream food webs as the key source of energy and nutrients for macroinvertebrates.…”
Section: Discussionmentioning
confidence: 69%
“…Connectance values for Charcote and Charcotico were low compared to values reported for other terrestrial and aquatic food webs, some with estimates as high as 4 (Hewatt, 1937;Paine, 1966Paine, , 1980Menge, Sutherland, 1976;Dunne et al, 2002). Schmid-Araya et al (2002) concluded that connectance of stream food webs is lower than in other types of ecosystems. Low connectance of stream food webs may be associated with body size disparity within food chains, disturbance associated with flow variation, and heterogeneity and complexity of stream habitats (Schmid-Araya et al, 2002).…”
Section: Discussionmentioning
confidence: 86%
“…Schmid-Araya et al (2002) concluded that connectance of stream food webs is lower than in other types of ecosystems. Low connectance of stream food webs may be associated with body size disparity within food chains, disturbance associated with flow variation, and heterogeneity and complexity of stream habitats (Schmid-Araya et al, 2002). Differences between connectance of our trophic networks based on fish diets and connectance values reported in studies that analyzed published food web diagrams could be methodological artifacts; for example, our food webs have many nodes but lack trophic links between invertebrates and their food resources, and most published food web diagrams contain few nodes, with many nodes consisting of highly aggregated taxa or functional groups (Paine, 1988;Winemiller, 1990;Cohen et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…grasslands and rainforest) and aquatic (freshwater and marine) environments suggest that network robustness increases with connectance Thompson et al, 2012). In comparison with surveys conducted by Martinez (1991) in Little Rock Lake (USA) and Schmid-Araya et al (2002b) in different ecosystems across the UK, our biocoenotic analysis was conducted over small spatial distances, within short time periods, and among shallow water bodies with slight habitat differences. The empirical data-sets collected in this study could be used for further food web simulations and could contribute to comparative studies among diverse ecosystem networks (Bascompte, 2009).…”
Section: Discussionmentioning
confidence: 99%